2023
DOI: 10.1051/0004-6361/202244749
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the differences in rotational support among early-type galaxies: The case of galaxies outside clusters

Abstract: Context. Early-type galaxies (ETGs) are divided into slow and fast rotators (FRs and SRs) according to the degree of ordered rotation of their stellar populations. Cosmological hydrodynamical simulations indicate that galaxies form as FRs before their rotational support decreases, usually because of mergers. Aims. We aimed to investigate this process observationally for galaxies outside of clusters. Methods. We made use of the fact that different merger types leave different traces that have different lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 219 publications
(304 reference statements)
3
3
0
Order By: Relevance
“…The histograms presented in the lower panels of for the two ETG categories provides p = 1.8 × 10 −15 , indicating a highly significant difference between the two distributions. This result aligns with those reported in previous studies (Bílek et al 2020(Bílek et al , 2023Yoon & Lim 2020).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The histograms presented in the lower panels of for the two ETG categories provides p = 1.8 × 10 −15 , indicating a highly significant difference between the two distributions. This result aligns with those reported in previous studies (Bílek et al 2020(Bílek et al , 2023Yoon & Lim 2020).…”
Section: Resultssupporting
confidence: 94%
“…Since dynamical friction can make the infall orbit of satellite galaxies more radial, massive satellites are more likely to be accreted through radial orbits in the later stages of mergers (Amorisco 2017;Pop et al 2018). This could explain our observational result that shell-type tidal features are detected in slightly more massive ETGs, which is also found in the simulation of Pop et al (2018) and in the observation of Bílek et al (2023). We note that low-mass satellites require almost purely radial infall orbits at the initial accretion time in order to produce shells in the simulation of Pop et al (2018).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Note that our analysis is based on a sample of active star-forming galaxies that mostly include disks. Recently, Bílek et al (2023) reported that earlytype galaxies with lower rotational support tend to have more negative metallicity gradients.…”
Section: Discussionmentioning
confidence: 99%